Dante and the Mediterranean Comedy - Celli, Andrea. author. (orcid)0000-0001-7848-957X Link aut Link
XIII, 278 p. 6 illus. in color.
Keywords: “Celli’s work stands at the forefront of a new generation of scholars who seek to revise fundamentally our understanding of Dante, and literary works more generally, in terms of the broader Mediterranean world and across religious traditions and historical eras. The originality of Celli’s approach cannot be overstated, and indeed it renders difficult any attempt to confine him to a specific disciplinary category.” —William Caferro, Gertrude Conaway Vanderbilt Professor of History, Vanderbilt University “One of the most notable aspects of Celli’s scholarship, at work in this book, is the ease with which he moves from the most minute detail to the large picture. Or rather, he is remarkably adept at showing how the smallest action-such as an anonymous reader’s substituting a word in the margin of a printed obituary-can expose what is at stake not only across someone’s academic career but also across distinct disciplines and historical time periods.” —Jo Ann Cavallo, Professor of Italian, Columbia University In recent decades the concept of Mediterranean has been cited with increasing frequency in relation to the study of medieval literatures. And yet, in what sense would Dante’s Comedy be ‘Mediterranean’? Is it because of its Greek-Arabic and Islamic sources? Dante and the Mediterranean Comedy analyzes the ideological function of references to the sea in the study of the Comedy undertaken by Enrico Cerulli, a scholar of Somali-Ethiopian languages, and a colonial governor of ‘Italian East Africa.’ Then it presents novel lines of inquiry on the reception and appropriation of the poem, such as the presence of Islamic sources in early commentaries of the Comedy, and cross-cultural allusions to Dante’s Hell in some graffiti on the walls of the Spanish Inquisition prison in Palermo. The image of the Mediterranean that seeps through the poem and through the history of its circulation is vivid yet hardly idyllic. Andrea Celli is Associate Professor of Italian and Mediterranean Studies at the University of Connecticut, USA.